PROCESSING OF THE STRATEGIC SEQUENCE OF DIAGNOSTIC PATIENTS WITH TEMPOMANDIBULAR DISORDERS AND OCCLUSIVE INTERFERENCES - T.I. Pupin; A.Yu. Fetsych (Український стоматологічний альманах)
Temporomandibular joint pathology in combination with the development of pathological processes in the muscles and cranial dysfunction manifests as a complicated clinical picture, which leads to difficulties in diagnostic. In the diagnostics of disorders of the neuromuscular apparatus and the temporomandibular joint, modern clinical, instrumental, functional and radiological examination methods are widely used with biomechanical digital analysis, which require systematization.